2011
DOI: 10.4028/www.scientific.net/amr.317-319.1559
|View full text |Cite
|
Sign up to set email alerts
|

Design of a DSP System Based on FPGA

Abstract: This paper proposes an innovative methodology to design a DSP (Digital Signal Processing) system using FPGA (Field-programmable Gate Array). There are several main components in this system, including A/D sampling unit, FFT processing unit and control unit. A/D sampling and FFT processing units utilize the Nios processor in FPGA as controller. Control unit uses EP1C20 FPGA chip from ALTERA as FFT processing unit so as to manage the FIFO operations. This unit can handle 128 FFT operations. This system design ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Activated carbon is a good metal catalyst support. Since their better catalytic activation, the activated carbons supported transition metals were studied by more and more researchers all over the world [3][4][5][6][7][8]. F.Luckin [3] treated the chlorphenol wastewater with an activated carbon supported Fe, the results indicated that Fe had a good catalytic property.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon is a good metal catalyst support. Since their better catalytic activation, the activated carbons supported transition metals were studied by more and more researchers all over the world [3][4][5][6][7][8]. F.Luckin [3] treated the chlorphenol wastewater with an activated carbon supported Fe, the results indicated that Fe had a good catalytic property.…”
Section: Introductionmentioning
confidence: 99%